Impact of COVID-19 on the Use of Emergency Contraceptives in Ghana: An Interrupted Time Series Analysis - Fuseini, Kamil; Jarvis, Leah; Hindin, Michelle J.; Issah, Kofi; Ankomah, Augustine (Frontiers in Reproductive Health, 2022)
The Coronavirus disease pandemic has disrupted reproductive health services including decline in the use of pre-coital contraceptives. However, evidence of its impact on the use of emergency contraceptives, often, post-coital methods, is limited in the emerging literature, hence this study. Data on total number of emergency contraceptive users from January 2018 to February 2020 (pre-pandemic) and March to December 2020 (during the pandemic) were extracted from the Ghana Health Service District Health Information Management System. Interrupted Time Series analysis was used to estimate the impact of the pandemic on the trend of emergency contraceptive use, adjusting for serial autocorrelation and seasonality. The results showed a gradual upward trend in emergency contraceptive use before the pandemic, increasing at a rate of about 67 (95% CI 37.6–96.8; p = 0.001) users per month. However, the pandemic caused a sudden spike in the use of emergency contraceptives. The pandemic and its related restrictions had an immediate effect on the use of emergency contraceptives, increasing significantly by about 1939 users (95% CI 1096.6–2781.2; p = 0.001) in March 2020. Following March 2020, the number of emergency contraceptive users continued to increase by about 385 users per month (95% CI 272.9–496.4; p = 0.001). The evidence shows that use of emergency contraceptives, often used as post-coital methods for unprotected sex was not negatively impacted by the pandemic. In fact, it is the opposite. Hence, in planning for similar situations attention should be given to the distribution of post-coital contraceptive methods.